A brief chronology of librarianship in Russia: status and prospects of development - E. A. Pleshkevich (Библиосфера, 2018)
The article provides an overview of the chronological table on the history of the national librarianship prepared by the Russian State Library staff. The chronology covers over 1,250 library and related events and facts that took place in the period from the mid XI-XX centuries. The paper reveals basic methodological problems of chronological surveys and gives methodical recommendations to overcome them. It notes that the foundation to construct the chronological table should be a model of historical development on which basis is the selection of specific events. The author shows the most significant events of the library history in details and in this way separates them from others.